PEMBENTUKAN KECAMATAN KAPUAS SELATAN KABUPATEN SANGGAU BERDASARKAN PERATURAN PEMERINTAH NOMOR 17 TAHUN 2018 TENTANG KECAMATAN - NIM. A1011141154, NURISTI TRI WULANDARI (Jurnal Fatwa Hukum, 2024)
ABSTRACTNuristi Tri Wulandari, 2021. Formation of South Kapuas District, Sanggau Regency Based on Government Regulation Number 17 of 2018 concerning Districts. The aim of this research is to determine the factors that influence the implementation of the formation of South Kapuas District, Sanggau Regency, based on Government Regulation Number 17 of 2018 concerning Districts and the efforts made by the regional government of Sanggau Regency in order to realize the formation of South Kapuas District. The research method used is a type of normative legal research with descriptive research characteristics. The results of this research indicate that the process of establishing the expansion of South Kapuas District in Sanggau Regency refers to Government Regulation Number 17 of 2018 concerning Districts and Law Number 23 of 2014 concerning Regional Government. The factors causing delays in the implementation of the formation of the South Kapuas District expansion area in Sanggau Regency are due to the incomplete completion of the Sanggau District Regulation for the technical requirements listed in Article 5 of Government Regulation Number 17 of 2018 concerning Districts, and the finances of the Sanggau Regency government which has temporarily allocated funds for handling Covid-19 cases. 19. Meanwhile, the efforts being made by the Sanggau Regency government in the process of implementing the formation of the South Kapuas District expansion area in Sanggau Regency for now is to wait for the process of implementing the Sanggau District Regulation to be completed and handle the Covid-19 case so that it can re-implement the process of establishing the South Kapuas District area in Sanggau Regency. The advice that can be given is that in the process of forming a new sub-district expansion area, it is necessary to re-evaluate the provisions and requirements that must be met, so that there are no human errors when the implementation of the formation of the sub-district expansion area is carried out.Keywords: Regional Expansion, South Kapuas District, Government Regulation Number 17 of 2018.ABSTRAK  Nuristi Tri Wulandari, 2021. Pembentukan Kecamatan Kapuas Selatan Kabupaten Sanggau Berdasarkan Peraturan Pemerintah Nomor 17 Tahun 2018 Tentang Kecamatan. Tujuan penelitian ini adalah untuk mengetahui faktor-faktor yang mempengaruhi pelaksanaan pembentukan Kecamatan Kapuas Selatan Kabupaten Sanggau Berdasarkan Peraturan Pemerintah Nomor 17 tahun 2018 tentang Kecamatan dan upaya yang dilakukan upaya pemerintah daerah Kabupaten Sanggau dalam rangka mewujudkan pembentukan Kecamatan Kapuas Selatan. Metode penelitian yang digunakan adalah jenis penelitian hukum normatif dengan sifat   penelitian deskriptif. Hasil penelitian ini menunjukkan bahwa dalam proses pembentukan pemekaran Kecamatan Kapuas Selatan di Kabupaten Sanggau mengacu pada Peraturan Pemerintah Nomor 17 Tahun 2018 tentang Kecamatan dan Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah. Faktor penyebab terhambatnya pelaksanaan pembentukan daerah pemekaran Kecamatan Kapuas Selatan di Kabupaten Sanggau dikarenakan belum selesainya Perbub Sanggau untuk persyaratan teknis yang tercantum dalam Pasal 5 Peraturan Pemerintah Nomor 17 Tahun 2018 tentang Kecamatan, dan keuangan pemerintahan Kabupaten Sanggau yang untuk sementara dialokasikan dananya terhadap penanganan kasus covid-19. Sedangkan upaya yang dilakukan pemerintah Kabupaten Sanggau dalam proses pelaksanaan pembentukan daerah pemekaran Kecamatan Kapuas Selatan di Kabupaten Sanggau untuk saat ini adalah menunggu proses pelaksanaan Perbub Sanggau selesai dilakukan dan menangani kasus covid-19 sehingga dapat melaksanakan kembali proses pembentukan daerah Kecamatan kapuas Selatan di Kabupaten Sanggau. Adapun saran yang dapat diberikan adalah dalam proses pembentukan daerah pemekaran kecamatan baru, diharuskan untuk mengevaluasi kembali ketentuan-ketentuan persyaratan-persyaratan yang harus dipenuhi, agar tidak terdapat kesalahaman (human error) ketika pelaksanaan pembentukan daerah pemekaran kecamatan tersebut dilakukan.  Kata Kunci : Pemekaran Daerah, Kecamatan Kapuas Selatan, Peraturan Pemerintah Nomor 17 Tahun 2018.